Comparative Study on Excitation Temperature, Electron Temperature and Electron Density in an Atmospheric Argon Microwave Plasma - 王仲 张贵新 刘程 贾志东 (Chinese physics letters, 2014)
An infinite-volume of atmospheric argon microwave plasma is produced in the microwave plasma source based on the inductive coupling window-rectangular resonator under the input of the microwave power at 2.45 GHz. The excitation temperature of the plasma is studied by using the Boltzmann plot of Ar I lines in two different wavelength ranges while the electron temperature is researched by using line-to-continuum intensity ratio of Ar I lines. The electron density is compared by using the Stark broadenings of At I lines at 522.13nm and 549.59nm and Ha line at 486.13nm.